The Analysis of Customer Satisfaction at Jagad Farm Binjai Grape Agrotourism in Tandem Hulu Village, North Binjai District, Binjai City, North Sumatra - Prayogi, Afrian; Nurcahyani, Marizha (Universitas Medan Area, 2025)
Competition among agrotourism destinations requires managers to maintain and improve service quality to meet visitors’ expectations. This study aims to analyze visitor satisfaction at Jagad Farm Grape Agrotourism using the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. Fourteen attributes covering product quality, service, facilities, and promotion were examined through visitor questionnaires. The results show a CSI value of 87.75%, categorized as “very satisfied,” indicating that most visitor expectations were met. The IPA results identified grape product quality, pre-visit promotion, and ease of understanding services as top priorities for improvement. Meanwhile, attributes such as product suitability, fair pricing, strategic location, and friendly service should be maintained. These findings recommend that management focus on enhancing priority attributes and maintaining those with good performance to ensure consistently high and sustainable visitor satisfaction.